SOCIAL ENGAGEMENT IN TEACHER DEVELOPMENT: UTILIZING PERFORMANCE APPRAISAL AS A TRAINING ASSIGNMENT STRATEGY - Taufik Churrahman; Nury Arsy Darmiati; Mochamad Nashrullah (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Education is the main foundation in shaping a thriving and sustainable society. The quality of instruction provided by teachers is a key factor in achieving optimal educational goals. This article explores the concept of social engagement in the context of teacher development with a focus on the utilization of performance appraisal as a strategy for determining training. Through a sociology of education perspective, this research aims to explore the complex relationship between social factors, interactions within the educational environment and the improvement of teacher professionalism. By integrating these concepts, this article details how teacher performance appraisals can be an effective foundation in establishing relevant training programs that positively impact their professional development. The method used in this study is Literature Review by reviewing three literatures related to research inclusion. Article searches were conducted through lens.org and google scholar. From the results of the study, it was found that the utilization of teacher performance appraisals was only utilized on the needs for payroll and promotion, not yet to the stage of determining the most needed training for teachers related to the results of performance appraisals. further evaluation of power dynamics, social interactions, and teacher participation in the performance appraisal process and determination of training is needed. This is important to achieve a more holistic and contextual approach to human resource management in education.